Landslide : The Unmaking of the President, 1984-1988 - Mayer, Jane; McManus, Doyle (Glasgow William Collins Sons & Company Ltd., 1989)
Gives a documented account of Reagan's second term and his failure to provide leadership.
Include Epilogue, Notes, Sources and Index.
Keywords: United States -- Politics and government -- Reagan, Ronald